Approved or disregarded? Exploring arenas for narrative relations in geriatric care - Lisa Herulf Scholander; Anne-Marie Boström; Staffan Josephsson; Sofia Vikström (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The use of narration in healthcare has been accentuated as a response to the requested shift towards person-centred care. The notion of narrative relations refers to a process of involving several people in mutual and ongoing narrative exchange. This study aimed to explore how and where narrative relations may be adopted and enacted in everyday healthcare practice. Methods The study has a qualitative, explorative design. Seven interprofessional focus group discussions with healthcare staff were prompted by vignettes. A multidisciplinary team of healthcare staff (n = 31) were recruited on a geriatric ward. Data were analysed using a constant comparative method. Results A core theme shows how narrative relations are adopted and enacted both as part of an approved practice—the work procedures commonly approved as part of healthcare, and as a disregarded practice where covert but important narrative relations take place to support fundamental qualities of healthcare. Moreover, the findings consider arenas of healthcare practice where approved or disregarded practices are enacted in the clinic frontstage and the clinic backstage. Conclusions Narrative relations may take place in different arenas of healthcare practice yet simultaneously become a cohesive force interconnecting those arenas and uphold continuity. Impeded narrative relations in one arena may have unintended consequences in another.